2016
DOI: 10.1590/0037-8682-0128-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of scorpions according to the socioeconomic conditions in Campina Grande,State of Paraíba, Brazil

Abstract: Introduction: Due to its frequency and morbidity, such as that caused by scorpions have achieved public health importance in certain regions of the world. The present exploratory ecological study aimed to characterize the epidemiological profi le and spatial distribution of scorpion stings in Campina Grande, State of Paraíba in Northeastern Brazil. Methods: Geographical information system techniques were used to record the scorpion stings, and Google Earth software, Track Maker, and ArcGIS 10 Esri were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
4
7
0
10
Order By: Relevance
“…The highest frequency of scorpion stings was observed in females compared to the male group of patients. These data corroborate results of other studies carried out in the Northeast region of Brazil 22,[24][25][26] . This exposure relationship can be explained by the longer period of time that women usually stay in the home environment, compared to men, as previously reported 27 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The highest frequency of scorpion stings was observed in females compared to the male group of patients. These data corroborate results of other studies carried out in the Northeast region of Brazil 22,[24][25][26] . This exposure relationship can be explained by the longer period of time that women usually stay in the home environment, compared to men, as previously reported 27 .…”
Section: Discussionsupporting
confidence: 92%
“…The elapsed time between the sting and early medical treatment is a crucial factor that greatly influences the prognosis of scorpion accidents 7 , as our study revealed that approximately 75% of all the patients received medical treatment up to 3 hours after the accident, in accordance with other previous studies [22][23][24]26,29 . In addition, in pediatric patients, a known risk group for scorpionism 9,37 , it was shown that prompt medical care may result in a better prognosis and therefore in mild cases 38 .…”
Section: Severitysupporting
confidence: 91%
“…Local and systemic symptoms of injury by scorpion are similar regardless of the zoological differences among these arachnids 43 . In our study, local symptoms were reported in 94.82% of the cases, which have also been reported in studies in the North 39 , Northeast 19 , 26 and other regions of Brazil 6 , 43 . Systemic symptoms were observed in 6.0% of the cases.…”
Section: Discussionsupporting
confidence: 89%
“…However, the risk of death was 1.39 times higher (0.868-2.238; p> 0.05) in men. The more regularly search for medical assistance by women may be related to the lower risk of death in cases of scorpion envenomation 26 . The highest frequency of cases involving the female gender was also reported in other States in the Northeast of Brazil 16 , 17 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Measures for the control and management of scorpions are based on scorpion removal/collection and modifying environmental conditions to become an unfavorable environment for the proliferation of these arachnids. This includes the active capture of scorpions where accidents are most frequent, indicated, for example, by geoprocessing or spontaneous population demand 12 . These measures can reduce the number of accidents and, consequently, the morbidity and mortality levels 2 .…”
Section: Dear Editormentioning
confidence: 99%